Indole-3-carboxamide alleviates LPS-induced endometritis through suppressing ferroptosis and inflammation via regulating Aryl hydrocarbon receptor - Chen, Feng; Cheng, Rujin; Chen, Xiangyang; Guo, Zhiheng (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeIndole-3-carboxamide (I3A), a derivative of tryptophan indole, has been reported to have anti-inflammatory role. This study aims to investigate the effects of I3A on LPS-induced endometritis in mice.MethodsThe mice endometritis model was established and I3A was administered to mice orally (150 mg/kg/day) for two days. TNF-α and IL-1β production were analyzed by ELISA. The protein expression was measured by western blot. The pathological changes of mouse uterine tissue were observed by H&E staining.ResultsThe experimental results showed I3A significantly alleviated LPS-induced uterine pathological injury. I3A treatment obviously attenuated LPS-induced MPO activity, TNF-α and IL-1β production. I3A also inhibited LPS-induced ferroptosis and NF-κB activation. Furthermore, I3A could up-regulate the expression of AhR and SLC7A11. The protective role of I3A on LPS-induced endometritis was reversed by AhR inhibitor CH223191.ConclusionIn conclusion, I3A inhibits LPS-induced endometritis in mice by attenuating inflammation and ferroptosis via the AhR-SLC7A11 signaling pathway.